1972
DOI: 10.1017/s0033291700042513
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of the syndrome of anorexia nervosa in male subjects

Abstract: SynopsisA syndrome characterized by the psychopathological features of anorexia nervosa occurs in male subjects. There have been 25 cases previously reported in the literature which appear to be fairly typical of the condition and the present paper adds the case histories of another six patients. Endocrine investigation on these patients reveals a disorder of urinary excretion levels of testosterone and of total gonadotrophic activity, which is comparable to the disturbance of sex hormones that accompanies the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(49 citation statements)
references
References 29 publications
5
44
0
Order By: Relevance
“…In AN the levels of the gonadotropins-the luteinizing (LH) and follicle-stimulating hormone (FSH)-in urine and blood are uniformly low in girls and boys following puberty (Beumont et al, 1972(Beumont et al, , 1973Buvat, Lemaire, Buvat-Herbout, Lepretre, & Fourlinnie, 1983;Brown et al, 1977;Danowski et al, 1973;Emanuel, 1956;Isaacs, Leslie, Gomez, & Bayliss, 1980;Lemaire et al, 1983;Lundberg et al, 1971;Marshall & Fraser, 1971;Russell et al, 1965;Wakeling & DeSouza, 1983;Warren & Vande Wiele, 1973). The reduction in E, levels can be accounted for by depressed resting urinary or serum luteinizing hormone (LH) and follicle-stimulating hormone (FSH) levels (Mecklenburg, Loriaux, Thompson, Anderson, & Lipsett, 1974).…”
Section: Gonadotropin Levelsmentioning
confidence: 99%
“…In AN the levels of the gonadotropins-the luteinizing (LH) and follicle-stimulating hormone (FSH)-in urine and blood are uniformly low in girls and boys following puberty (Beumont et al, 1972(Beumont et al, , 1973Buvat, Lemaire, Buvat-Herbout, Lepretre, & Fourlinnie, 1983;Brown et al, 1977;Danowski et al, 1973;Emanuel, 1956;Isaacs, Leslie, Gomez, & Bayliss, 1980;Lemaire et al, 1983;Lundberg et al, 1971;Marshall & Fraser, 1971;Russell et al, 1965;Wakeling & DeSouza, 1983;Warren & Vande Wiele, 1973). The reduction in E, levels can be accounted for by depressed resting urinary or serum luteinizing hormone (LH) and follicle-stimulating hormone (FSH) levels (Mecklenburg, Loriaux, Thompson, Anderson, & Lipsett, 1974).…”
Section: Gonadotropin Levelsmentioning
confidence: 99%
“…Although AN occurs mainly in females, its presentation in males has received extensive attention in the literature (Beumont, 1969;Beumont, Beardwood and Russell, 1972;Bruch, 1971;Crisp and Toms, 1972;Crisp, Burns and Bhat, 1986;Oyebode, Boodhoo and Schapira, 1988;Vandereycken and Van den Broucke, 1983). Nevertheless, the preponderance of female patients is not satisfactorily explained.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the lack of potency and sexual interest may be the male clinical equivalent to the female amenorrhea (Stephens, 1941;Aubert & Peigne, 1964;Ladewig, 1968). As Beumont et al (1972) state, however, concepts such as these are difficult to assess and quantify. Nevertheless, the hormones concerned with sexual functioning in the male can be the object of studies similar to those conducted with female patients.…”
Section: Endocrinologymentioning
confidence: 99%
“…The issue of homosexual conflict has already been discussed, and there may be abnormalities on CTT scans indicative of cerebral atrophe in men (Nussbaum et al, 1980). However, familial psychopathologies in males do resemble those of females, and many of the individual's psychopathological features resemble Anorcxia Ncrvosd in the Male 81 3 those of female anorexics (Crisp & Roberts, 1962;Roussounis, 1971;Beumont et al, 1972;Taipale et al, 1972;Hogan et al, 1974;Hay & Leonard, 1979).…”
Section: Sociocultural Influencesmentioning
confidence: 99%
See 1 more Smart Citation